Forming a Healthy Lifestyle culture in The Family in Adolescent Children - Karimova Gavhar Qudratilla qizi; Hoshimova Mohira Askhad qizi (Middle European Scientific Bulletin, 2021)
This article describes the role of thinkers in the formation of a healthy lifestyle in adolescents in the family, the views of thinkers on family relationships, the role of the family in the formation of a culture of healthy lifestyles in adolescents